Optimalisasi Waktu Pengomposan dan Kualitas Pupuk Kandang dari Kotoran Kambing dan Debu Sabut Kelapa dengan Bioaktivator PROMI dan Orgadec - Linda Trivana; Adhitya Yudha Pradhana (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Animal manures can be used as organic fertilizer because the high nutrient content such as nitrogen (N), phosphorus (P), and potassium (K). The nutrients are needed by plants and soil for fertility. One of the animal manuresthat can be used for organic fertilizer is goat manure. Goat manure is used as organic fertilizer it contains relatively more balanced nutrients than other natural fertilizer. In addition, the goat manure is mixed with the goat urine that alsocontains high nutrients. Coconut coir dust contains high potassium so that the addition of coconut coir dust in organic fertilizer will increase the potassium content (K) in organic fertilizer. The purpose of this research was to find out theinfluence of effective Orgadec and PROMI bioactivators on the optimal time of composting and the quality of the organic fertilizer. The organic fertilizer was analyzed to determine the content of N, P, K, organic-C, C/N ratio, watercontent, and pH. The result of analysis is compared with SNI 19-7030-2004. Organic fertilizer analysis was conducted on day 0, 10, 20, 30, 40, and 50. The result of the organic fertilizer analysis with Orgadec bio-activator more effectiveand faster on the decomposition organic matter in the compost compared PROMI (<20 days). The quality of organic fertilizer with Orgadec bioactivator on day 10 and 20, while organic fertilizer with PROMI on day 20, 30, 40, and 50days was in accordance with the quality stated in SNI 19-7030-2004 (C/N ratio, levels of N, P, K, water, and organic-C).